Tracking changes to a microplankton community in a North Atlantic sea loch using the microplankton index PI(mp). (18th August 2016) - Whyte, Callum; Davidson, Keith; Gilpin, Linda; Mitchell, Elaine; Moschonas, Grigorios; McNeill, Sharon; Tett, Paul
Abstract : Microplankton plays a vital part in marine ecosystems, and its importance has been recognized by the inclusion of microplankton community composition in regulatory frameworks such as the European Water Framework Directive and the Marine Strategy Framework Directive as an indicator of ecological status. Quantitative techniques are therefore required to assess the environmental status of the microplankton in a water body. Here we demonstrate the use of a method known as the microplankton index PI(mp) to evaluate changes in the microplankton community of the west coast Scottish Sea Loch Creran. Microplankton in this fjord has been studied since the 1970s, providing a data set spanning four decades. Our analysis compares an arbitrarily chosen reference period between 1979 and 1981 with a period between 2011 and 2013 and demonstrates that between these two periods community structure has changed considerably with a substantial drop in the numbers of observed diatoms accompanied by a rise in the number of autotrophic/mixotrophic dinoflagellates as well as an increase in the potentially toxin producing genus Pseudo-nitzschia and that these are related to changes in both the intensity and timing of local patterns of precipitation. The PI(mp) is shown to be a useful and robust method to visualize and quantify changes in the underlying structure of the microplankton community and is a powerful addition to the toolbox of techniques needed to determine the health of our seas.